2014
DOI: 10.1142/s0218127414300018
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations Leading to Nonlinear Oscillations in a 3D Piecewise Linear Memristor Oscillator

Abstract: In this paper, we make a bifurcation analysis of a mathematical model for an electric circuit formed by the four fundamental electronic elements: one memristor, one capacitor, one inductor and one resistor. The considered model is given by a discontinuous piecewise linear system of ordinary differential equations, defined on three zones in ℝ3, determined by |z| < 1 (called the central zone) and |z| > 1 (the external zones). We show that the z-axis is filled by equilibrium points of the system, and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Note that this relation does not involve the electric variables (v C , i C ). In the (ϕ, q)-domain the ideal capacitor C described by (20) admits of the equivalent circuit representation given in Fig. 3.…”
Section: B Constitutive Relationsmentioning
confidence: 99%
“…Note that this relation does not involve the electric variables (v C , i C ). In the (ϕ, q)-domain the ideal capacitor C described by (20) admits of the equivalent circuit representation given in Fig. 3.…”
Section: B Constitutive Relationsmentioning
confidence: 99%
“…Among various types of chaotic oscillators, Chua's canonical circuit is one of the most typical instances since it is simple and contains a wide range of dynamic behaviors. In many chaotic circuit studies, the constitutive relations of the memristors are non-smooth piecewise-linear functions, resulting in discontinuous nonlinear characteristics of the corresponding memristance (and memductance) [9,10,11]. Although most interesting chaotic phenomena and chaotic dynamics can be described by the piecewise-linear method; however, some subtle features of the real circuit may be missed by the piecewise-linear approximation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this makes the physical realization of such non-smooth memristors unrealistic [13]. Then, several chaotic circuit studies have been reported with smooth nonlinear memristors [13,14]; however, most of these published works are analytically developed with the numerical study without physical implantations [9,10,11,15]. As one of the most important perspective, controlling the behavior of the chaotic circuits is critical for chaos-based applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such system was reported [31], while other works [32,33] are dedicated to theoretical modeling of similar systems.…”
Section: Introductionmentioning
confidence: 99%